Effectiveness of Diabetes Mellitus Therapy - Artini, Kusumaningtyas Siwi; Jayak P, Kharisma; Hazir, Nur Shukriyah Binti Mohamad; Pahlawaningrum, Intan Malla (Global Health Science Group, 2024)
Diabetes mellitus is called the silent killer because this disease can affect all organs of the body and cause various kinds of complaints. Evaluation of the rationality of oral antidiabetic drugs on the effectiveness of therapy for patients with type II diabetes mellitus, RSUD Dr. Moewardi Surakarta concluded that ADO (biguanide + sulfonylurea) combination therapy is a therapy that is often used in patients and is effective in reducing blood glucose levels within 3 months of treatment. The aim of this study is to know the effectiveness of type II diabetes mellitus treatment therapy, both single treatment (oral or insulin) and combination (oral + oral or oral + insulin) which can reduce blood glucose levels in patients in the outpatient installation of RSUD Dr. Moewardi Surakarta in 2023. This research is non-experimental with retrospective data collection looking at patient medical record data. The sample size was calculated using the Slovin formula so that 88 respondents were obtained. Profile of treatment therapy used in type II diabetes mellitus patients undergoing outpatient treatment at RSUD Dr. Moewardi Surakarta has the most combination therapy of long-acting insulin + rapid-acting insulin with a percentage of 36.4%, then the second most is premixed analog insulin monotherapy with a percentage of 10.2%. The results of the paired sample T-test can be stated that from the 1st to the 2nd month there was a significant decrease in blood sugar levels as well as in the 1st to 3rd month, this indicates that antidiabetic drugs, both oral and injectable, are effective for lower blood sugar levels.